Effect of Replacement of Maize by Animal Fat on Growth and Nutrient Utilization of Growing Large White Yorkshire pigs - Elanchezhian, N; Ally, K. (Indian Journal of Animal Nutrition, 2020)
Â  Thirty weaned female Large White Yorkshire piglets were divided in to three groups with five replicates in each group and were maintained under identical management conditions for the period of 70 days.Â  The three dietary treatments were randomly allotted, T1-control ration as per NRC (1998), T2 -50 per cent of maize of control ration replaced by animal fat and T3-100 per cent of maize of control ration replaced by animal fat. The average daily gain and feed conversion efficiency were 813.00, 769.86, 678.43g and 2.80, 2.88, 3.08, respectively for three dietary treatments. The pigs of T1 had higher (P